WORKSHOP PEMBELAJARAN BERBASIS ICT PADA HMJ PGMI IAIN ANTASARI BANJARMASIN - Hamdan Husein Batubara; Dessy Noor Ariani (Universitas Islam kalimantan MAB, 2015)
The dedication of society service aims to increase students' insight and skills in using Information and Communication Technology (ICT) tools as media and learning resources that are believed to be effective in improving the quality of learning activities. Partners involved in science and technology for the society (IbM) is 25 students who are members of the Student Association of Elementary Teacher Education IAIN Antasari Banjarmasin. The methods of this activity is training in the form of tutorials and discussions about the steps of utilizing ICT as media and learning resources. The results show that the participants have understood the principles of ICT use in learning and are able to create learning media based ICT using PowerPoint applications.